Aplikasi Diagnosa Penyakit Tuberkulosis Menggunakan Metode Logika Fuzzy - Ma'ruf, Latif (AI Society & STMIK Indonesia, 2024)
Tuberculosis (TB) is a severe lung disease that often goes undetected because its symptoms are similar to those of a common cold. In 2022, Indonesia recorded over 700,000 TB cases, with one of the primary challenges being long hospital queues that delayed services. Advances in information technology, particularly in TB diagnosis, have the potential to speed up patient handling. With cases reaching 969,000 and 93,000 deaths annually, an early diagnosis system is essential to minimize delays. Fuzzy logic, an artificial intelligence approach, effectively manages uncertainty and complexity through